New species of Ipomoea (Convolvulaceae) from Bahia - Wood, J; Vasconcelos, L; Simão-Bianchini, R; Scotland, R (Springer Verlag, 2017)
Seven new species of Ipomoea are described from Bahia, Brazil: Ipomoea chapadensis J. R. I. Wood & L. V. Vasconc., I. parvibracteolata J. R. I. Wood & L. V. Vasconc., I. connata J. R. I. Wood & L. V. Vasconc., I. pterocaulis J. R. I. Wood & L. V. Vasconc., I. queirozii J. R. I. Wood & L. V. Vasconc., I. longibracteolata Sim.-Bianch. & J. R. I. Wood and I. magna Sim.-Bianch. & J. R. I. Wood. The species are illustrated with line drawings and photographs, their distinguishing characters and relationships are discussed, their distribution is mapped and their conservation status is assessed.